The rise of the knowledge society. - Drucker, Peter F. (Wilson Quarterly)
Explains why knowledge is more essential than capital and labor in the global economy of the 1990s. Rise of the knowledge society; Radical changes in the meaning of knowledge; Social transformation of society brought about by Capitalism and the Industrial Revolution; Management Revolution from 1945 to the 1990s; Changes in the form and content of knowledge.